Candi: A Malaysian-tailored dietary smartphone app for cancer patients and survivors - Lin, L.P; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Mohd Razif, Shahril; Aryati, Ahmad; Noor Solihah, Zakaria (2016)
Smartpltone-based interventions such as mobile apps have been shown to be effective in promoting healthy dietary behaviour. To-date however, smartphone apps are scarcely available for our local commmuniities and the majority of nutritional-related information is based on western food selections. Cancer patients and survivors in particular, continue to suffer from appetite problems and nutritional deficits, either as a result of disease manifestation or treaturent side effects. Our new innovation aims to provide specific educational advice about recommended food intake, types, nutritional qualities and weight issues for such patients. The Cancer Dietary (CanDi) App represents a convenient, flexible and attractively engaging smartphone app containing healthy tips which are uniquely tailored to the local food choices, preferences and ingredients. This helps customise users' dietary needs besides permitting constant information up-dating. Features are broadly categorised into Health Eating Guide and Malaysian Recipes For Cancer Patients. The former category includes advice from healthy eating to eating problems, prevention of weight loss and increasing proteins and calories. In the latter, common Malaysian dishes, ingredients, treatment-based recipes and special diets are focused. There is also an additional Symptom Diary allowing the personal profile of user to be recorded. With this scientific yet creative innovation, routine dietary habits related to cancer conditions could be easily facilitated for both patients/survivors as well as family caregivers for their independent and healthy living.